Meningkatkan Kemampuan Guru dalam Menyusun RPP Mengintegrasikan Pendidikan Berkarakter melalui Bimbingan Berkelanjutan Di SDN Teluk Tiram 2 Banjarmasin - Norjenah (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
One the development values character thoroughly to give you syllabus values character in implementation plan (lesson plans and learning) made teachers.In this is an aptitude or competence of teachers to arrange a syllabus and lesson plans in which values is the insertion of character. To know teacher capacity building sdn the gulf of oysters 2 banjarmasin in preparing lesson plans that integrates character education. Method used in research the act of this school reduce research the act of class. Steps research is planned 2 cycles. Research is based on the context natural namely examine issues factual in the preparation of device planning learning , that is a syllabus and lesson plans. The research results show that the teacher capacity building and lesson plans in implementing syllabus characterless, in I cycle 52,08 % to 87,5 % in II cycle. So expressed guidance syllabus and lesson plans to significant characterless increased. There has been increasing the capability of teachers in carrying out to characterless syllabus, where I cycle 57,41 % to 88,89 % in II cycle.Guidance for teachers at the school sustainable activities is to increase ability to plan education learning that integrates characterless in sdn the gulf of oysters banjarmasin 2.